2020
DOI: 10.1021/acsami.0c06964
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity, Stability, and Loading Trends of Alcohol Dehydrogenase Enzyme Encapsulated in a Metal–Organic Framework

Abstract: Recently, it has been shown that enzyme encapsulation inside metal–organic frameworks (MOFs) can increase enzyme activity and serve as protection from adverse environmental conditions. Little is understood about how the enzymes move into and are held inside the MOFs although it is believed that intermolecular forces between the MOF and the enzyme cause it to be held in place. If this process can be better understood, it can have dramatic implications on the cost-effectiveness and implementation of enzyme–MOF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 67 publications
(112 reference statements)
3
24
0
Order By: Relevance
“… 51 Recent publications have reported the successful immobilization of different enzymes within the pore network of PCN-333, including horseradish peroxidase (HRP), 51 cytochrome c (Cyt c), 51 microperoxidase-11 (MP-11), 51 catalase (CAT), 52 superoxide dismutase (SOD), 52 and alcohol dehydrogenase (ADH). 53 In this study, we have selected two commercially available enzymes of different sizes for the immobilization experiments: lipase (3.0 × 4.0 × 5.0 nm 3 ) 54 and insulin (1.3 × 1.3 × 3.4 nm 3 ) 55 ( Figure 1 c). Lipase is a commercially important enzyme that catalyzes hydrolysis reactions, 56 and insulin is an important medical hormone responsible for regulating the concentration of glucose in blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“… 51 Recent publications have reported the successful immobilization of different enzymes within the pore network of PCN-333, including horseradish peroxidase (HRP), 51 cytochrome c (Cyt c), 51 microperoxidase-11 (MP-11), 51 catalase (CAT), 52 superoxide dismutase (SOD), 52 and alcohol dehydrogenase (ADH). 53 In this study, we have selected two commercially available enzymes of different sizes for the immobilization experiments: lipase (3.0 × 4.0 × 5.0 nm 3 ) 54 and insulin (1.3 × 1.3 × 3.4 nm 3 ) 55 ( Figure 1 c). Lipase is a commercially important enzyme that catalyzes hydrolysis reactions, 56 and insulin is an important medical hormone responsible for regulating the concentration of glucose in blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Very early during our study, water has shown to be an ineffective media for cytochrome c diffusion into NU-1000. Since previous reports have shown that buffer concentration influences enzyme loading in a different system through the PSE technique ( Phipps et al., 2020 ), we first explored encapsulation conditions for obtaining the cyt c @NU-1000 composite using Tris buffer at four different concentrations (0.00 M, 0.25 M, 0.50M, and 0.90 M). Prior to assessing the composites’ activities, we examined the structural integrity of the resultant materials.…”
Section: Resultsmentioning
confidence: 99%
“…All electrochemical measurements, including cyclic voltammetry (CV) chronoamperometry and electrochemical impedance spectroscopy (EIS), were performed on an electrochemical workstation (CHI 660E, Shanghai Chenhua Instrument Co., Ltd., China). Although we have tested the intrinsic resistance of AuNPs/NFPBA and NFPBA through BDS, considering that the biosensor was working in buffer, EIS was further applied to investigate the resistance of electron transfer ( R ct ) in solution 40 . EIS characterization was carried out in the presence of 5 mM [Fe(CN) 6 ] 3−/4− solution containing 0.1 M KCl, the frequency ranges were also from 0.01 Hz to 10 MHz.…”
Section: Methodsmentioning
confidence: 99%